Optimasi Pengaturan Kecepatan Motor Shunt Berbasis Imperalist Competitive Algorithm (ICA) - Machrus Ali; Agus Raikhani; Hendi Sopian; Izzatul Umami (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
Imperalist Competitive Algorithm (ICA) is one method of artificial intelligence inspired by competition for power. In system optimization this method gets better results than other artificial intelligence methods. DC shunt motors do not need a lot of space because of the small wire diameter, but the output power is very small because the amplifier current is small. A good shunt motor setting is needed to produce the desired motor speed. In this study PID controls were tuned using ICA. This good PID guide will get a good system optimization. As a comparison, the control of the shunt motor speed without control, with PID control, with detuning ICA PID control (PID-ICA). The results showed that the results of PID-ICA had the smallest overshot and undershot, with a speed of 500.00 rpm and the fastest settling time : 1201 s. This research will be developed using other artificial intelligence methods.